The BSN-PhD/DNP education programmes in nursing: a scoping review protocol - Qirong Chen; Ruiqi Zhang; Minhui Liu; Peibei Yuan; Kehan Liu (BMJ Open, 2025)
Introduction To address evolving healthcare challenges, developing advanced clinical-academic nursing talent has become imperative. Bachelor of Science in Nursing - Doctor of Philosophy/Doctor of Nursing Practice (BSN-PhD/DNP) education programmes create structured pathways that connect the undergraduate and postgraduate training processes, enabling the systematic identification and development of clinical academic talent through a vertically integrated education programme. However, related literature is fragmented, and training processes remain unclear. This protocol is for a scoping review that aims to synthesise existing information about the training process (eg, admission, examinations and curriculum) and barriers and facilitators to implementing this education programme to enhance the development of a high-quality BSN-PhD/DNP education programme.Methods and analysis The scoping review will be conducted following the methodological guidelines provided by the JBI guidelines. The scoping review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for the Scoping Reviews checklist. Literature will be retrieved from PubMed, Web of Science, Cochrane Library, EMBASE, SCOPUS, ERIC, CINAHL, Proquest, EBSCO, CNKI, Wanfang and VIP on March 16, 2025. Additionally, grey literature, such as official websites of the top 50 or 100 nursing universities ranked by QS and Google searches, will be reviewed. Two researchers will extract data independently from the eligible literature. Discrepancies will be addressed through discussions with other researchers. The results will be displayed in both tables and written format.Ethics and dissemination This study does not require ethical approval. We will disseminate our results in peer-reviewed journals and present at conferences relevant to the field of nursing education.Trial registration number This scoping review protocol has been registered on Open Science Framework (https://osf.io/9xwnj).